IMPLEMENTASI STATIC APPLICATION SECURITY TESTING MENGGUNAKAN JENKINS CI/CD BERBASIS DOCKER CONTAINER PADA PT. EMPORIA DIGITAL RAYA - Abriza Mahandis Shama; Dian W. Chandra (JURNAL ILMIAH INFORMATIKA, 2021)
PT. Emporia Digital Raya is an fintech company. The product include web and android application. However, in the deployment system, PT Emporia Digital Raya still uses an ancient system with a single vm system and only uses git for deployment to server. Even though at this time the deployment process of an application has grown very far. Therefore, in this study will created a system which is currently popular being used. This system is called DevSecOps. Devsecops will need a tools like Jenkins, Sonarqube, and Docker. The core of this system is the automation process where the deployment process is no longer done manually as before. With this system, it is hoped that will help speed up developer work and improve code quality.